Regeneration of coelomocytes after evisceration in the sea cucumber, Apostichopus japonicus. Issue 76 (May 2018) - Li, Qiang; Ren, Yuan; Liang, Chunlei; Qiao, Guo; Wang, Yinan; Ye, Shigen; Li, Ruijun
Abstract: Sea cucumber, Apostichopus japonicus, is one of the most important holothurian species cultured in China. Severe evisceration induced by various natural and artificial factors commonly occurs during transport and culture of A. japonicus. Evisceration causes higher mortality and lower yield. Along with the visceral regeneration process, sea cucumbers also regenerate coelomocytes in order to recover immune function. In this study, evisceration of A. japonicus was induced by intracoelomic injection of 0.35 M KCl. Regeneration of coelomocytes was investigated by time course cell counting as well as detection of DNA replication by the EdU labeling technique. Coelomic fluid volume was restored to the pre-evisceration level within 2 h after evisceration. Total coelomocyte count (TCC) reached a peak at 6 h post-evisceration, followed decreased and then increased with a slight fluctuation, restored to the pre-evisceration level at 35 d post-evisceration. The change in different subtypes of coelomocytes was consistent with that of total coelomocytes. However, there were some variations in the regeneration of coelomocyte subtypes. At the end of the study, only the counts of amoebocytes and morula cells recovered to the pre-evisceration level. DNA replication assay showed EdU-positive cells accounted for 9.5% before evisceration and 4.7% at 6 h post-evisceration. However, the percentage of EdU-positive cells significantly increased, reaching 18.6% at 3 d after evisceration, then declined. Therefore, we analyzed the observed increase in coelomocytes at 6 h post-evisceration, which may be due to coelomocyte migration from the water-vascular system into the coelom rather than de novo cell proliferation. Highlights: All the coelomocytes were recovered at 35d after evisceration. Regeneration stage of coelomocytes was divided into two periods. Sharp increase period might be due to coelomocyte migration from the water vascular system of A. japonicus.